Analysis of the Influence of Online Reviews, Service Quality, And Cleanliness on Consumers' Intentions to Visit Legendary Restaurants Around Jakarta Old Town - John Pier Christian Israel Boanerges; Valisca Valisca; Vasco A. H. Goeltom; Wulanmeiaya Wowor (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to investigate the impact of online reviews, service quality, and cleanliness on consumers' decisions to visit renowned restaurants in Jakarta's Old Town area. The research employs a combination of observation, visitor interviews, and both qualitative and quantitative data analysis. The results indicate that online reviews play a significant role in shaping consumers' intentions to visit, while service quality and cleanliness also have a notable impact on their choices. The study underscores the importance of managing online reputations and upholding excellent cleanliness standards to increase the attractiveness of legendary restaurants. It aims to provide actionable recommendations for restaurant owners to enhance the overall customer experience.